Prolonged complete atrioventricular block due to neostigmine and amiodarone interaction in an amyloidosis patient with left main dissection and postoperative intestinal pseudo-obstruction. Issue 3 (31st March 2022) - Kalogerakos, Paris-Dimitrios; Lasithiotakis, Konstantinos; Vernardos, Michail; Lazopoulos, Lambros; Koutsopoulos, Anastasios; Lazopoulos, George
ABSTRACT: Cardiac amyloidosis has been strongly associated with postoperative intractable circulatory failure, and intestinal amyloidosis could lead to intestinal pseudo-obstruction. The latter can be treated with neostigmine, which is notorious for its brief bradyarrhythmic complications. The amyloidosis patient presented herein, suffered an iatrogenic left main dissection, failure of bailout stenting and finally underwent urgent surgery. Meticulous fluid and drug management was key to keeping this patient stable. Postoperative atrial fibrillation was treated with amiodarone. The postoperative course was complicated with intestinal pseudo-obstruction, which was ultimately resolved with neostigmine. This short-lived cholinesterase inhibitor interacted with amiodarone and caused a previously undocumented prolonged complete atrioventricular block that resolved 48 hours after both drugs' discontinuation. The neostigmine amiodarone interaction warrants clinical vigilance and is speculated to be due to their partially shared second messenger pathway involving cyclic adenosine monophosphate. Patients with cardiac amyloidosis could maintain hemodynamic stability perioperatively.